2018
DOI: 10.3390/ijfs6030077
|View full text |Cite
|
Sign up to set email alerts
|

How Do Investment Banks Price Initial Public Offerings? An Empirical Analysis of Emerging Market

Abstract: This study investigates that how investment banks select alternative valuation models to price Initial Public Offerings (IPOs) and examine the value-relevance of each valuation model using the data of 88 IPOs listed on the Pakistan Stock Exchange (PSX) during 2000–2016. This study investigates that investment banks used Dividend Discount Model (DDM), Discounted Cash Flow (DCF) and comparable multiples valuation models on the basis of firm-specific characteristics, aggregate stock market returns and volatility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 54 publications
2
13
1
Order By: Relevance
“…That comparable firm has designated a benchmark for determining the IPO offering price (Kim & Ritter, 1999). This method takes into account the relative value of assets of a competitive firm and then prices the shares of the IPO company based on this relative value using various financial indicators (Agnes Cheng & McNamara, 2000;Rasheed, Khalid Sohail, Din, & Ijaz, 2018).…”
Section: Methods Of Ipo Pricingmentioning
confidence: 99%
See 1 more Smart Citation
“…That comparable firm has designated a benchmark for determining the IPO offering price (Kim & Ritter, 1999). This method takes into account the relative value of assets of a competitive firm and then prices the shares of the IPO company based on this relative value using various financial indicators (Agnes Cheng & McNamara, 2000;Rasheed, Khalid Sohail, Din, & Ijaz, 2018).…”
Section: Methods Of Ipo Pricingmentioning
confidence: 99%
“…The most popular method used in the comparable firm approach for the valuation of IPOs is the dividend discount model. That model is based on the proposition that the value of a firm's stock is equal to the discounted value of the infinite cash flow of the expected dividends per share (Rasheed, Khalid Sohail, Din, & Ijaz, 2018;(Gacus & Hinlo, 2018;Sim & Wright, 2017). The other approach firm analysis for the IPO valuation is the discounted cash flow method.…”
Section: Methods Of Ipo Pricingmentioning
confidence: 99%
“…They explain that underwriters deliberately overestimate IPOs to justify applying high levels of discounts. Rasheed et al (2018), Roosenboom (2012) and Tutuncu (2020) find that discounts depend on valuation optimism. Additionally, Cassia et al (2004), Paleari et al (2014) and Vismara et al (2015) find that underwriters perform a biased selection of peers to overestimate IPOs.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 98%
“…Actually, only a limited number of studies examining IPOs discounts can be found due to the public unavailability of such information. Most of these studies report that discounts are applied to FVE before setting FOP (Cassia et al, 2004;Deloof et al, 2009;Paleari et al, 2014;Rasheed et al, 2018;Roosenboom, 2012;Tutuncu, 2020;Vismara et al, 2015). They explain that underwriters deliberately overestimate IPOs to justify applying high levels of discounts.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation